Application of a geographic information system in the study of spatial aspects of cervical cancer incidence in Belgrade - Pavlović, Nevenka; Marković Denić, Ljiljana; Vojvodić, Katarina (Vojnosanitetski pregled, 2021)
Background/Aim. Cervical cancer is still an important public health problem in Belgrade. The aim of this study was to explore spatial patterns of cervical cancer, provision and accessibility of women’s health service on the primary health care level in Belgrade, as well as the needs for improving cancer surveillance and preventive programs. Methods. This study applied a descriptive epidemiological method and a geographic information system based on data on cervical cancer diagnosed among female residents of Belgrade in 2006 and 2011. A map of the density of cases, with precise and complete data on the address of residence at the time of diagnosis, and a map of the distribution of gynecological practices in the primary health care in Belgrade, were generated through the process of georeferencing. Results. A total of 569 cases of cervical cancer were registered in 2006 and 2011, without significant differences. Significant associations were noticed for municipality of residence and year of diagnosis (χ2= 42.99, df = 16, p = 0.000), and year of diagnosis and age groups 30–34 (р = 0.038, f = 3.998, df = 11, ANOVA), 40–44 (р = 0.001, f = 7.545 df = 13, ANOVA) and 45–49 (р = 0.046, f = 2.679, df = 15, ANOVA). The process of georeferencing covered a total of 466 (81.8%) cases with 97.4% of all cases diagnosed in 2006 and 68.6% in 2011. The generated maps showed similar spatial patterns of cases for both years: a higher density of cases with addresses in central parts of urban and suburban municipalities, as well as in parts of densely populated areas of urban municipalities. There was no regularity of grouping found for the cases in relation to the provision of women’s health service, or of distance from the place of residence of cases to gynecological practices. Conclusion. Our results indicate possibilities for the perception of the spatial distribution of cervical cancer and needs for improving cancer surveillance and preventive programs on small geographical areas.
Keywords: epidemiologic methods; geographic information systems; primary health care; urban population; uterine cervical neoplasms